Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
the article describes a theoretical study of the professional readiness of a leader to implement the GEF of preschool education, the development of a competency model of the head of a preschool educational organization, the main components of which are general cultural, motivational and axiological, cognitive, social and communicative, managerial, and also personal and creative.
Keywords: дополнительное профессиональное образование; профессиональная компетентность; компетенция; professional competence; competence; Федеральный государственный образовательный стандарт дошкольного образования; federal state educational standard of preschool education; additional professional education